The Use of a Constructivist Grounded Theory Method to Explore the Role of Socially-Constructed Metadata (Web 2.0) Approaches - Alemu, Getaneh; Stevens, Brett; Ross, Penny; Chandler, Jane (Qualitative and Quantitative Methods in Libraries, 2017)
Purpose –This paper provides rationale for using a constructivist grounded theory method for PhD research in Library and Information Research, entitled “Towards a Theory of Digital Library Metadata: The emergence of Enriching and Filtering”. It highlights on the processes of data collection using intensive interviewing and three stages of data analysis, namely: open coding, focused coding andtheoretical coding. In addition, the processes of constructivist grounded theory conceptualisation using memo writing and theoretical saturation are highlighted. Design/methodology/approach –While the actual results of the PhD study will be presented separately, this paper mainly focuses on the best practises and lessons learnt from the adoption of the method. The paper highlights on how the method enabled the researcher to conduct iterative scrutiny of the concepts and categories through the method‟s memo writing and conceptualisation processes four core categories have emerged. It is argued that a constructivist grounded theory approach is fitting to address issues in relation to Web 2.0 and user-driven metadata approaches.    Findings –Following a rigorous application of the method, a constructivist grounded theory method is considered appropriate to explore emerging areas of research in library and information science. It is indicated that the novelty of the use of web 2.0 and social media in libraries, the issue of socially-constructed metadata approaches is relatively under-developed and thus there are absence of extant theories, suggesting thus the importance of inductive research methods, such as the constructivist grounded theory method presented in this paper.Taking into account, the potential existence of diversity of views among librarians, LIS researchers, metadata experts and library users with respect of the issues of involving users in metadata creation, from the three approaches to grounded theory, Charmaz‟s (Charmaz, 2006) constructivist approach was considered fitting. Practical implications –The case for the viability of the constructivist grounded theory method for high level research such as PhD, is made. It is believed that LIS researchers who aim to undertake a research on emerging topical issues, such as Web 2.0, would find the method appropriate. The method allows two-way mutual co-constructions of concepts between the researcher and research participant.  It also provides the researcher flexibility and rigour to gather views and opinions, through interactive and iterative indepth interviews.It also allows the researcher to analyse and interpret the perspectives of participants‟ through identification of concepts and categories from the data collected. Finally, the method is expected to help to develop a theory that overarches the concepts and categories derived from the data collected.